Wilhelm Röpke (1899-1966) A Liberal Political Economist and Conservative Social Philosopher (The European Heritage in Economics and the Social Sciences,, 2018)
This volume provides a comprehensive account of Wilhelm Röpke as a liberal political economist and social philosopher. Wilhelm Röpke (1899-1966) was a key protagonist of transatlantic neoliberalism, a prominent public intellectual and a gifted international networker. As an original thinker, he always positioned himself at the interface between political economy and social philosophy, as well as between liberalism and conservatism. Röpke's endeavors to combine these elements into a coherent whole, as well as his embeddedness in European and American intellectual networks of liberal and conservative thinkers, are a central theme throughout the book. The volume includes papers by international experts from a conference in Geneva on the occasion of the 50th anniversary of Röpke's passing. The first part focuses on new biographical insights into his exile years in Istanbul and Geneva, while the second part discusses his business cycle theory in the context of the Great Depression, and the third part elaborates on his multifaceted social philosophy. Wilhelm Röpke was among the most important thinkers within the classical liberal revival post-WWII, with intriguing tensions between liberalism and conservatism. A highly recommended volume. -- Peter J. Boettke, 2016-2018 President of the Mont Pèlerin Society and Professor of Economics and Philosophy, George Mason University This important collection of papers provides an in-depth assessment of Wilhelm Röpke's contributions, placing him in the context of his time. A fine contribution. -- Bruce J. Caldwell, Director of the Center for the History of Political Economy and Research Professor of Economics, Duke University.